The Experience of Pleasure: A Perspective Between Neuroscience and Psychoanalysis - Moccia, Lorenzo; Mazza, Marianna; Nicola, Marco Di; Janiri, Luigi (Frontiers in Human Neuroscience, 2018)
Pleasure is more than a mere sensory event, but rather it can be conceptualized as a complex, multiform experience involving memory, motivation, homeostasis and, sometimes, negative affects. In “Instincts and their Vicissitudes”(1915) Freud defined drive as a “a measure of the demand made upon the mind to work in consequence of its connection with the body”, underlining both drive bodily nature and its quantitative characteristics. According to Freud, affect is a perceptual modality that registers the internal state of the subject rather than the objective experience of the external world, and the quality of this perceptual modality is calibrated in degrees of pleasure and displeasure. Within this conceptual framework, the aim of drive is always pleasure, and objects become significant in so far as they provide a way of discharging drives pressure. Later in “Beyond the Pleasure Principle”(1920) Freud attempted to better clarify the nature of pleasure and its relationship with drive by introducing the concepts of repetition compulsion and death instinct. Consistently with Freud’s theory, pleasure corresponds to a diminution of “unbound” drive excitation, while displeasure corresponds to an increase of it. Subsequent conceptual psychoanalytic developments have partially rejected such metapsychological theorizations, postulating that drives are primarily object-seeking, rather than pleasure-seeking. The notions of pleasure, drives and affects are all of utmost importance for a neuropsychoanalytic understanding of mental functioning, due to their capability to explain desire, thought and behavior from the perspective of human subjective experience. Thus, the purpose of this paper is to discuss psychoanalytic conceptual developments that have addressed pleasure, drives and affects, in the light of recent findings coming from neurosciences. In particular, we will explore for insights from Panksepp’s theory of primary-process emotional feelings, including the notion of “wanting” and “liking” as dissociable components of reward. In the last part of the paper, we will briefly indicate possible theoretical implications for a neuropsychoanalytic understanding of human motivations that are independent from libido, including the sense of agency and attachment.